Hair manifestations in factory workers with arsenic exposure in Hayatabad industrial estate Peshawar, Pakistan - Mahvish Javed; Zilli Huma; Zeeshan Kibria; Muhammad Adeel Alam Shah (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: Arsenic is present both naturally and from manmade sources like factory effluents. Contamination by arsenic of the groundwater is a major source of health detriment in south-east Asian countries. The aim of this study was to identify levels of arsenic in drinking water sources and factory effluents and to analyse arsenic levels in hair samples from factory workers and their families, along with morphological changes in hair in industrial workers in Peshawar.METHODOLOGY: Water and hair samples were collected by random sampling from a labor colony of 81 factory and non-factory household members living and working in the same industrial estate and analyzed for arsenic. Hair morphology was carried out in histomorphology laboratory at Khyber Medical University, Peshawar. The results obtained from both groups were compared with normal hair histomorphology. The data was analyzed by using SPSS version 20.RESULTS: The arsenic level in drinking water, colony tube wells and households was not within the permissible level of WHO (10µg/L). The arsenic level in factory effluent was 68µg/l (Pakistan Government's acceptable level is 50µg/L). The difference was statistically significant p≤0.001 between the two groups, the factory workers had a relatively higher level of arsenic, ~34ppb, in their scalp hair. Hair arsenic level also came out to be <1.00µg/g. There was a wide variation in the histomorphology of the hair samples in both groups.CONCLUSION: Elevated levels of arsenic in factory effluent demonstrate improper decontamination. The arsenic levels were within permissible levels, long term effects cannot be ruled out.